Synthesis and characterisation of composite partially phosphorylated polyvinyl alcohol-aluminium phosphate as protective coating - Saat, A.M.; Latiff, N.A.; Yaakup, S.; Johan, M.R. (International Union of Crystallography, 2014)
Partially phosphorylated polyvinyl alcohol-aluminium phosphate was synthesised through continuous stirring and condensation at 80 degrees C. The compositions of the resulting phosphorylated polyvinyl alcohol-aluminium phosphate samples were varied, by adjusting the ion ratio and concentration of complex forming additives in the electrolyte solution. The as-synthesised phosphorylated polyvinyl alcohol-aluminium phosphate was then subjected to various chemical, thermal and structural characterisations. Fourier transform infrared studies show the bonding between phosphorylated polyvinyl alcohol and ALPO(4) at phosphate containing group. Differential scanning calorimetric studies show that T-g, T-m and degree of crystallinity increase as ALPO(4) filler was added to the system. Electrochemical impedance spectroscopy analysis shows good promising new inhibitor material for mild steel immersed in NaCl medium.